Combination therapy is superior to sequential monotherapy for the initial treatment of hypertension: A double-blind randomized controlled trial - MacDonald, TM; Williams, B; Webb, DJ; Morant, S; Caulfield, M; Cruickshank, JK; Ford, I; Sever, P; Mackenzie, IS; Padmanabhan, S; McCann, GP; Salsbury, J; et al. (American Heart Association, Inc., 2017)
Background--Guidelines for hypertension vary in their preference for initial combination therapy or initial monotherapy, stratified by patient profile; therefore, we compared the efficacy and tolerability of these approaches. Methods and Results--We performed a 1-year, double-blind, randomized controlled trial in 605 untreated patients aged 18 to 79 years with systolic blood pressure (BP) ≥150 mm Hg or diastolic BP ≥95 mm Hg. In phase 1 (weeks 0-16), patients were randomly assigned to initial monotherapy (losartan 50-100 mg or hydrochlorothiazide 12.5-25 mg crossing over at 8 weeks), or initial combination (losartan 50-100 mg plus hydrochlorothiazide 12.5-25 mg). In phase 2 (weeks 17-32), all patients received losartan 100 mg and hydrochlorothiazide 12.5 to 25 mg. In phase 3 (weeks 33-52), amlodipine with or without doxazosin could be added to achieve target BP. Hierarchical primary outcomes were the difference from baseline in home systolic BP, averaged over phases 1 and 2 and, if significant, at 32 weeks. Secondary outcomes included adverse events, and difference in home systolic BP responses between tertiles of plasma renin. Home systolic BP after initial monotherapy fell 4.9 mm Hg (range: 3.7-6.0 mm Hg) less over 32 weeks (P < 0.001) than after initial combination but caught up at 32 weeks (difference 1.2 mm Hg [range: -0.4 to 2.8 mm Hg], P=0.13). In phase 1, home systolic BP response to each monotherapy differed substantially between renin tertiles, whereas response to combination therapy was uniform and at least 5 mm Hg more than to monotherapy. There were no differences in withdrawals due to adverse events. Conclusions--Initial combination therapy can be recommended for patients with BP > 150/95 mm Hg.